The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1002/biot.201500055
|View full text |Cite
|
Sign up to set email alerts
|

The stage‐specific in vitro efficacy of a malaria antigen cocktail provides valuable insights into the development of effective multi‐stage vaccines

Abstract: Multicomponent vaccines targeting different stages of Plasmodium falciparum represent a promising, holistic concept towards better malaria vaccines. Additionally, an effective vaccine candidate should demonstrate cross-strain specificity because many antigens are polymorphic, which can reduce vaccine efficacy. A cocktail of recombinant fusion proteins (VAMAX-Mix) featuring three diversity-covering variants of the blood-stage antigen PfAMA1, each combined with the conserved sexual-stage antigen Pfs25 and one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 28 publications
5
23
1
Order By: Relevance
“…In agreement with our earlier DiCo-based studies (37, 44) and those reported by other groups (19, 45), we observed balanced IC 50 values (~150 μg/ml) against different strains. This is in contrast to using single alleles for immunization, where the IC 50 values in GIA are significantly higher (greater than twofold) for heterologous compared to homologous (vaccine-like) strains (18).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with our earlier DiCo-based studies (37, 44) and those reported by other groups (19, 45), we observed balanced IC 50 values (~150 μg/ml) against different strains. This is in contrast to using single alleles for immunization, where the IC 50 values in GIA are significantly higher (greater than twofold) for heterologous compared to homologous (vaccine-like) strains (18).…”
Section: Discussionsupporting
confidence: 93%
“…The DiCo1-3 sequences (Figure S1 in Supplementary Material) were amplified from their source constructs (37) and introduced into the plant expression vector pTRAkc-ERH (linearized with Nco I/ Not I) in-frame with an upstream signal peptide sequence and a downstream His 6 tag and SEKDEL signal for retention in the endoplasmic reticulum (38). Additionally, six different alleles of Pf AMA1 ( Pf AMA1-3D7, Pf AMA1-FCR3, Pf AMA1-HB3, Pf AMA1-Dd2, Pf AMA1-7G8, and Pf AMA1-RO33) were obtained as synthetic genes codon optimized for N. benthamiana from Geneart (Thermo Fisher Scientific, Waltham, MA, USA) and introduced into the plant expression vector pTRAkc-ERH using the cloning strategy mentioned above.…”
Section: Methodsmentioning
confidence: 99%
“…CFCA data have been successfully correlated to growth inhibition in vaccine development (Spiegel et al 2015) and for the identification of biomarkers Shah et al 2015).…”
Section: Applicationsmentioning
confidence: 99%
“…29 Overall, our predicted data provide a strong rationale for developing asexual blood-stage vaccine component as part of a multivalent effective malaria vaccine that may need to incorporate antigens of several life-cycle stages including liver stage. [64][65][66][67] …”
Section: Resultsmentioning
confidence: 99%